2012
DOI: 10.1073/pnas.1116092109
|View full text |Cite
|
Sign up to set email alerts
|

Strong relationship between elemental stoichiometry and metabolome in plants

Abstract: Shifts in the elemental stoichiometry of organisms in response to their ontogeny and to changing environmental conditions should be related to metabolomic changes because elements operate mostly as parts of molecular compounds. Here we show this relationship in leaves of Erica multiflora throughout their seasonal development and in response to moderate experimental field conditions of drought and warming. The N/P ratio in leaves decreased in the metabolically active growing seasons, coinciding with an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
209
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 231 publications
(231 citation statements)
references
References 46 publications
15
209
0
1
Order By: Relevance
“…The observed metabolic shifts associated with organisms N:P ratio change 21 provide support for the hypothesis that exceedances of the optimal N:P ratios can reduce growth rates 34 . Several studies have verified this hypothesis in diverse unicellular organisms, zooplankton and fish in aquatic ecosystems; there is evidence that this hypothesis can also be extended to a large number of terrestrial plants and animals, albeit with a few exceptions 35 (Fig.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The observed metabolic shifts associated with organisms N:P ratio change 21 provide support for the hypothesis that exceedances of the optimal N:P ratios can reduce growth rates 34 . Several studies have verified this hypothesis in diverse unicellular organisms, zooplankton and fish in aquatic ecosystems; there is evidence that this hypothesis can also be extended to a large number of terrestrial plants and animals, albeit with a few exceptions 35 (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…In the Mediterranean shrub Erica multiflora, for instance, increases in N:P ratio were accompanied by decreased proportions of primary metabolites (sugars, amino acids) relative to lipids and secondary metabolites, and also by lower growth rates 21 . Several studies have observed that the N:P ratio of foliage correlates negatively with net photosynthetic rate 22 , plant growth 23 and biomass production 24 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent stoichiometric ecological studies have shown that K is even more associated than is N or P with stoichiometric differences among various plant ecotypes (Sardans and Peñuelas, 2014;Sardans et al, 2012c) or with stoichiometric shifts in response to environmental changes (Rivas-Ubach et al, 2012). The strong link between plant K concentrations and water availability (Sardans et al, 2012c;Yavitt et al, 2004) justifies the study of K and its stoichiometric relationships with other nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, independently of the FL, the concentrations of sugars, phenolics, and amino acids such as proline (Figure 4c,d) in summer were higher in iberica than nevadensis needles, also suggesting that iberica experienced more stress in summer. In previous ecometabolomic studies, we have also observed increases in sugar, amino acid, and phenolic concentrations in different plant species during the dry summers of the Mediterranean climate (Rivas‐Ubach et al., 2012, 2014; Rivas‐Ubach, Barbeta, et al., 2016). Proline is an important osmoprotectant in plants (Szabados & Savouré, 2010), so the higher proline concentrations in the needles of iberica compared to nevadensis also suggest that this subspecies may be facing more intense drought conditions in Sierra Nevada than those in its native range in Navacerrada (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolome is the chemical phenotype of an organism (Fiehn, 2002) and is the first to respond to biotic and abiotic stressors (Peñuelas & Sardans, 2009). The recent application of new metabolomic techniques in the fields of plant physiology and ecology (ecometabolomics) has allowed the detection of the extreme plasticity of metabolomes under different environmental situations (Rivas‐Ubach, Sardans, Pérez‐Trujillo, Estiarte, & Peñuelas, 2012; Rivas‐Ubach, Barbeta, et al., 2016; Sardans, Peñuelas, & Rivas‐Ubach, 2011). However, the metabolome, as any other aspect of the phenotype, can also be subject to evolutionary divergence given that metabolic responses ultimately depend on genetic composition and expression (Riedl et al., 2012).…”
Section: Introductionmentioning
confidence: 99%